Pengendalian Kecemasan, Persiapan Mental Sebelum Latihan, dan Bertanding pada Permainan Sepak Bola - atiq, ahmad; Purnomo, Edi; Ali, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
This study aims to determine the status of anxiety control mental preparation before training and competing in soccer games. This research uses a quantitative descriptive method with survey techniques. The type of research used in this research is quantitative descriptive research, using a survey method with a research design that is a retrospective causal-comparative design. The population of this study was 20 football players at the PS Untan Football Club. This research instrument uses the Psychological Skills Inventory for Sports (PSIS) scale, which consists of controlling anxiety and mental preparation. The data analysis technique used is one-way ANOVA. The results of the research showed that, on average, soccer athletes majoring in sports science experienced nine anxiety controls in the excellent category, with a percentage of 43%. In the moderate category, there were six players, with a percentage of 30%, and in the fair category, there were five athletes, 26%. For the mental preparation of 20 athletes, eight people (17.30%) had good mental preparation status, six people (34.60%) had moderate mental preparation status, five people (39.2%) had mental preparation status and two people (8.7%) had mental preparation. In conclusion, controlling anxiety and mental preparation of football players falls into the moderate category, so coaches and players must always pay attention to training patterns that increase anxiety control, mental preparation, and paying attention before training, matches, and in training and competitions in line with after training and competitions too. Keywords: Anxiety Control, Mental Preparation Before Training, and Competing in Football Games